Antibacterial activity of new peptide from bovine casein hydrolyzed by a serine metalloprotease of Lactococcus lactis subsp lactis BR16. (May 2017) - Bougherra, Fateh; Dilmi-Bouras, Abdelkader; Balti, Rafik; Przybylski, Rémi; Adoui, Faiza; Elhameur, Hacene; Chevalier, Mickaël; Flahaut, Christophe; Dhulster, Pascal; Naima, Nedjar
Highlights: The use of a serine metalloprotease with a particular mode of action on casein. Application of adsorption and desorption method to purify antimicrobial peptides. Purification and identification of a new antibacterial peptide from αs2 casein. Abstract: An extracellular serine metalloprotease produced by Lactococcus lactis subsp lactis BR16 isolated from Algerian traditional fermented food was used for hydrolyzing bovine casein in order to identify antibacterial peptide. Antibacterial peptide was separated from peptic hydrolysates by adsorption/desorption then analyzed using reverse phase high performance liquid chromatography (RP-HPLC) and active fraction was analyzed by MALDI-TOF mass spectrometry. A new antibacterial peptide was identified as SSSEESII from the subunit αs2 of casein corresponding of the fragment (24–31). This peptide demonstrated antibacterial activity against two Gram-positive bacteria: Listeria innocua ATCC 33090 and Micrococcus luteus ATCC 4698, and two Gram-negative bacteria: Escherichia coli ATCC 25922 and Salmonella enteritidis ATCC13076. Prediction of peptide secondary structure indicated that this peptide is anionic and must have random coil structure with a small region of hydrophobicity, which confers to the peptide unusual behavior compared to conventional antimicrobial peptides.